Comparison of data acquisition modes with Orbitrap high‐resolution mass spectrometry for targeted and non‐targeted residue screening in aquacultured eel. (19th February 2020) - Wu, I‐Lin; Turnipseed, Sherri B.; Storey, Joseph M.; Andersen, Wendy C.; Madson, Mark R.
Abstract : Rationale: A current trend in monitoring chemical contaminants in animal products is to use high‐resolution mass spectrometry (HRMS). In this study, several HRMS data acquistion modes using Orbitrap MS for simultaneous full‐scan MS in combination with MS2 analysis were evaulated for their effectiveness in detecting and identifying both targeted and non‐targeted veterinary drug residues in aquacultured eel samples. Methods: Sample preparation consisted of an acidic acetonitrile extraction with solid‐phase extraction cleanup for analysis using LC/HRMS. Different data acquisition methods, including full‐scan MS with non‐targeted all ion fragmentation (AIF), multiplexed or variable data‐independent analysis (mDIA or vDIA), targeted data‐dependent MS2 (DDMS2), and parallel reaction monitoring (PRM) acquisition, were explored. The methods were evaluated with fortified eel tissue and imported eel samples to determine how many analytes could be detected and identified. Results: For non‐targeted data acquisition, the number of analytes detected using DIA methods matched the results obtained by AIF, but the resulting product ion scans were more diagnostic because characteristic ions were predominant in the DIA MS2 spectra. In targeted analysis for a limited list of 68 compounds, full‐scan MS followed by PRM was advantageous compared with DDMS2 because high‐quality MS2 spectra were generated for almost all the analytes at target testing levels. Conclusions: For residue screening, AIF has fast MS1 scan speed with adequate detection of product ions but may lead to false positive findings. DIA methods are better suited to monitor for both targeted and non‐targeted compounds because they generate more characteristic MS2 spectra for retrospective library searching. For follow‐up targeted analysis, PRM is prefered over DDMS2 when searching for a limited set of compounds.